Variation in genes involved in epigenetic processes offers insights into tropically adapted cattle diversity - Porto-Neto, Laercio R.; Fortes, Marina R. S.; McWilliam, Sean M.; Lehnert, Sigrid A.; Reverter, Antonio (Frontiers in Genetics, 2014)
We evaluated the relevance of the BovineHD Illumina SNP chip with respect to genes involved in epigenetic processes. Genotypes for 729,068 SNP on two tropical cattle breeds of Australia were used: Brahman (n = 2,112) and Tropical Composite (n = 2,550). We used data mining approaches to compile a list of bovine protein-coding genes involved in epigenetic processes. These genes represent 9 functional categories that contain between one (histone demethylases) and 99 (chromatin remodelling factors) genes. A total of 3,091 SNP mapped to positions within 3,000 bp of the 193 coding regions of those genes, including 113 SNP in transcribed regions, 2,738 in intronic regions and 240 in up- or down-stream regions. For all these SNP categories, we observed differences in the allelic frequencies between Brahman and Tropical Composite cattle. These differences were larger than those observed for the entire set of 729,068 SNP (P = 1.79 x 10-5). A multidimensional scaling analysis using only the 113 SNP in transcribed regions allowed for the separation of the two populations and this separation was comparable to the one obtained with a random set of 113 SNP (Principal Component 1 r2 > 0.84). To further characterise the differences between the breeds we defined a gene-differentiation metric based on the average genotypic frequencies of SNP connected to each gene and compared both cattle populations. The 10% most differentiated genes were distributed across 10 chromosomes, with significant (P < 0.05) enrichment on BTA 3 and 10. The 10% most conserved genes were located in 12 chromosomes. We conclude that there is variation between cattle populations in genes connected to epigenetic processes, and this variation can be used to differentiate cattle breeds. More research is needed to fully characterise the use of these SNP and its potential as means to further our understanding of biological variation and epigenetic processes.